‫أﺛﺮ‬‫ﺗﻜﻠﻔﺔ‬ ‫اﻷﻣﻮال‬ ‫ﻋﻠﻰ‬ ‫ﺗﺴﻌﻴﺮ‬ ‫اﻟﻘﺮض‬ ‫اﻻﺳﺘﻬﻼﻛﻲ‬ ‫ﻓﻲ‬ ‫اﻟﺒﻨﻚ‬ ‫اﻟﻮﻃﻨﻲ‬ ‫اﻟﺠﺰاﺋﺮي‬ - ‬‫أﺣﻼم ‫ﻏﻠﻮﺳﻲ ‬ (My University, 2017)
The bank credits are used by new banks for commercial use. This will teach us how to find a new credit card or a new bank account. Algerians, this is the consummation credit, and also to determine the global share of their memories and The resources used in the finance process and their impact on the cost of the project The consumption is limited to the definition, the condition and its effects on the national economy and on Individually, as soon as the cloth is covered for its amenities, and the cloth is covered with rain and prêts. And to donate to this city a more realistic and logical definition, given the bank situation. Algerians commercialize our homes as an example of the National Bank of Algeria BNA.